2020
DOI: 10.1016/j.eimc.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

First identification of blaNDM-1 carbapenemase in blaOXA-94-producing Acinetobacter baumannii ST85 in Spain

Abstract: Introduction: NDM-1 carbapenemase is spreading rapidly all over the world, but this metallo-betalactamase has just been detected for the first time in an Acinetobacter baumannii (Ab) isolate of the ST85 clone in Spain. The aim of this study was to characterize a NDM-1-producing carbapenem-resistant A. baumannii (CR-Ab) isolate submitted to the Andalusian PIRASOA [infection prevention program] referral laboratory. Methods: Carbapenemases were detected by PCR and Sanger DNA sequencing. Whole genome sequencing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…ST85 is represented by two isolates (AB177-VUB and AB186-VUB), yet only AB177-VUB possesses both bla NDM-1 and bla OXA-94 . A. baumannii ST85 possessing the bla NDM-1 and bla OXA-94 genes was previously detected in France, Algeria, Turkey, Syria, Tunisia, and, recently, also Spain (22). AB186-VUB possesses bla OXA-94 but not bla NDM-1 , pointing toward geographical unrelatedness of AB177-VUB and AB186-VUB.…”
Section: Resultsmentioning
confidence: 93%
“…ST85 is represented by two isolates (AB177-VUB and AB186-VUB), yet only AB177-VUB possesses both bla NDM-1 and bla OXA-94 . A. baumannii ST85 possessing the bla NDM-1 and bla OXA-94 genes was previously detected in France, Algeria, Turkey, Syria, Tunisia, and, recently, also Spain (22). AB186-VUB possesses bla OXA-94 but not bla NDM-1 , pointing toward geographical unrelatedness of AB177-VUB and AB186-VUB.…”
Section: Resultsmentioning
confidence: 93%
“…The ST1089 (IC9) strains were the second most common lineage in this study. These strains have been isolated from clinical samples and hospital environments, particularly from studies in Northern Africa and in the Middle East, and are frequently reported to carry blaNDM-1 and blaOXA-94 carbapenem resistance genes (32,(33)(34)(35)(36)(37)(38)(39). An ST1089 strain carrying blaNDM-1 was also isolated from raw milk in a dairy farm in Algeria (40).…”
Section: Discussionmentioning
confidence: 99%
“…New Delhi Metallo-β-Lactamase-6 (NDM-6) has a similar hydrolyzing activity as NDM-1 and has been mainly reported in members of the Enterobacterales family to date (Williamson et al, 2012;Rahman et al, 2014;Bahramian et al, 2019). NDM-1-like derivative enzymes have been reported in carbapenem resistant Gram-negative organisms from multiple countries worldwide (Berrazeg et al, 2014;Dortet et al, 2014) including European countries, e.g., Germany, Switzerland, Slovenia, France, Belgium, Czech Republic, and very recently also in Southern Spain (Pfeifer et al, 2011;Bonnin et al, 2012;Fernandez-Cuenca et al, 2020). However, in the region of the Basque Country (Northern Spain), no NDM-like-enzymes have been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…ST85 A. baumannii, carrying bla OXA-94 and bla NDM-1 , recovered from Syrian civil war victims were first reported from Lebanon (Rafei et al, 2014). Furthermore, isolates encoding bla OXA-94 and bla NDM-1 were also reported from Southern Spain, Saudi Arabia, and Tunisia, or harboring bla VIM-1 in Egypt, indicating that the novel IC9 clonal lineage has a widespread distribution and was found repeatedly harboring MBLs (Jaidane et al, 2018;Al-Hassan et al, 2019;Al-Hamad et al, 2020;Fernandez-Cuenca et al, 2020). cgMLST analysis using currently available complete genomes of ST85 Pas A. baumannii isolates revealed that the AbBAS-1 isolate is closely related (81 alleles difference) to an NDM-1-positive CRAB isolated in Southern Spain in 2017 ( Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%